أثر تطبيق نظام البصمة الاالكترونية على الضغوط المهنية بالمؤسسة الجامعية - عسيلة ماريا; عموري اكرام (University Of Eloued جامعة الوادي, 2024)
Study Abstract The current study aimed to investigate the relationship between the implementation of an electronic fingerprint system and occupational stress among employees of the Faculty of Arts and Languages at the University of Shahid Hameed Laghrar in Ouled Djellal. The study was based on the following hypotheses: -Working with an electronic fingerprint system affects the workload of faculty employees. -Working with an electronic fingerprint system affects role ambiguity among faculty employees. -Working with an electronic fingerprint system affects role conflict among faculty employees. The study employed a descriptive approach and utilized a questionnaire as the primary tool for data collection. The study sample consisted of 54 employees from the Faculty of Arts and Languages at the University of Shahid Hameed Laghrar in Ouled Djellal. The study yielded several key findings, including: -There is no significant relationship between the implementation of an electronic fingerprint system and occupational stress among faculty employees. -The electronic fingerprint system does not cause fatigue or exhaustion among faculty employees. -Unclear policies and procedures regarding the fingerprint system lead to imbalance
دراسة ميدانية بكلية الأداب واللغاب بجامعة الشهيد حمه لخضر الوادي
Keywords: الضغوط المهنية; Pressions professionnelles; Professional pressures; البصمة الإلكترونية; Empreinte digitale électronique; Electronic fingerprint